Money, Sex and Broken Promises: Politicians' Bad Behaviour Reduces Trust - Richard Rose; Bernhard Weßels (Parliamentary Affairs, 2019)
This article develops and tests empirically a theory of the effect on political trust of forms of behaviour that violate social, political and legal norms about how politicians ought to behave. These include taking money for favours, over-indulging in private life and making misleading promises to win votes. The evidence comes from a specially designed survey in Britain, France and Spain, countries where popular distrust of politicians appears greater than illegal political behaviour. Bad behaviours, especially abandoning election promises once in office, have a much stronger effect on distrust of political parties that do differences in partisanship. Comparing national regressions shows that the impact of bad behaviours is very similar in Britain, France and Spain.
Keywords: 330; distrust; mandate; misleading voters; MPs'; behaviour; over-indulgence; taking money